2020
DOI: 10.1038/s41598-020-63949-x
|View full text |Cite|
|
Sign up to set email alerts
|

Baroreceptor denervation reduces inflammatory status but worsens cardiovascular collapse during systemic inflammation

Abstract: Beyond the regulation of cardiovascular function, baroreceptor afferents play polymodal roles in health and disease. Sepsis is a life-threatening condition characterized by systemic inflammation (SI) and hemodynamic dysfunction. We hypothesized that baroreceptor denervation worsens lipopolysaccharide (LPS) induced-hemodynamic collapse and SI in conscious rats. We combined: (a) hemodynamic and thermoregulatory recordings after LPS administration at a septic-like non-lethal dose (b) analysis of the cardiovascula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…We also investigated the effects of SI on haemodynamic parameters in SHR and Wistar rats. In Wistar rats, LPS administration induces characteristic biphasic drop in MAP associated with tachycardia (Saia et al 2013;Amorim et al 2019Amorim et al , 2020. On the other hand, the LPS-induced drop in MAP was significantly higher in SHR than in Wistar rats, whereas LPS-induced tachycardia was blunted in these animals ( Fig.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…We also investigated the effects of SI on haemodynamic parameters in SHR and Wistar rats. In Wistar rats, LPS administration induces characteristic biphasic drop in MAP associated with tachycardia (Saia et al 2013;Amorim et al 2019Amorim et al , 2020. On the other hand, the LPS-induced drop in MAP was significantly higher in SHR than in Wistar rats, whereas LPS-induced tachycardia was blunted in these animals ( Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Considering the existing evidence regarding the reduction in the baroreflex gain in SHR rats (Head & Adams, 1988), as well as our own data, we suggest that the reduction baroreflex gain in SHR rats is one of the mechanisms involved in the enhancement of the LPS-induced drop in blood pressure in SHR. Regarding HR, a blunted tachycardia with greater drop in blood pressure in SHR may be related, at least in part, to the baroreflex (Amorim et al 2019(Amorim et al , 2020. Recent studies have suggested that endovascular baroreflex amplification therapy, which increases the stretch of the carotid and sinus activating the baroreceptors, may be a good alternative in the management of hypertensive patients who are resistant to anti-hypertensive medication (van Kleef et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations